Efficacy of Levocetirizine, Prednisolone and their combination in the treatment of chronic urticaria: a comparative study - More, Kanhaiah; Samskar, B.; Simpson, G. B. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Urticaria results from many different stimuli and numerous factors like immunologic, non-immunologic, genetic and modulating factors which are involved in its pathogenesis and ultimately converge on mast cells and basophils to release mediators and produce urticarial lesions. This study is aimed to compare the therapeutic effectiveness of Levocetirizine (newer generation H1 blocker), prednisolone (glucocorticoid) and their combination in the treatment of chronic urticaria. Methods: Group I (34 patients received tab Levocetirizine alone 5mg daily for 15 days). Group II (33 patients received tab Prednisolone alone 20mg /day for initial 3 days and later dose was gradually tapered by 5mg /day every 3 days to 5mg/day with total duration of 12 days). Group III (33 patients received the combination of Levocetirizine and Prednisolone). Results: The Group -I patients average eosinophil count before and after treatment was 4±1.4 and 2.4±0.8 respectively, with an average difference of 1.7±1.3. In Group - II patients average eosinophil count before and after treatment was 4.0±1.1 and 2.5±0.3 respectively, with an average difference of 1.5±1.1. In the Group - III patients the average eosinophil count before and after treatment was 4.3±1.0 and 2.1±1.0 with an average difference of 2.2±1.3. In G-I (n=34). Conclusions: Statistical analysis of the present study showed that the combination of Levocetirizine and prednisolone therapy was significantly (P<0.05) greater than prednisolone alone therapy and improvement with Levocetirizine alone (79%) was almost similar to combination therapy (85%).